Percutaneous Vertebroplasty for Osteolytic Spinal Lesion. A Pilot Study - Mohamed Amer (Egyptian Spine Association, 2013)
Background Data: The clinical management of osteolytic spinal lesion is unique, because it is challenging to approach these lesions. Surgery and/or radiotherapy has been the treatments of choice for many years; but, surgery may not be an option for patients with multiple spinal lesion and poor general medical status, and radiotherapy carries the risk of vertebral collapse and consequent neural compression. Through different approaches, vertebroplasty has been introduced into clinical practice as an alternative to traditional surgery and radiotherapy of osteolytic spinal lesion. Purpose: To evaluate the safety and efficacy of percutaneous vertebroplasty for selected patients with osteolytic vertebral compression fractures (VCFs). Study Design: Retrospective descriptive clinical case study. Patients and Methods: Between March 2009 and April 2014, fifteen patients with back pain due to primary or secondary vertebral neoplasm were treated with vertebroplasty. The patients were followed up for 3-6 months, with an average of 5.4 months. The clinical effects regarding back pain were evaluated with the visual analog scale (VAS) preoperatively and at 3 days, one month, 3 months and 6 months post-operatively. Results: Fifteen patients (9 males and 6 females) were treated by vertebroplasty. The age ranged from 20 to 60 years with a mean of 44.25 years. All patients presented by severe disabling back pain. The dorsal spine was affected in nine patients followed by lumbar spine in five patients and only one case in the cervical spine. The pathology was primary tumor in nine patients and secondary in six cases. All patients had a satisfying resolution of their painful symptoms postoperatively. Two cases of cement leakage were reported without major complication. Conclusion: Percutaneous Vertebroplasty is an effective technique to treat osteolytic spinal lesions. It is a valuable, minimally invasive, and efficient method that allows quick and lasting local resolution of painful symptoms. (2013ESJ058)